2018
DOI: 10.1590/01047760201824042571
|View full text |Cite
|
Sign up to set email alerts
|

MULTIPLICATION OF Cattley guava BY DIFFERENT TECHNIQUES AND VARIABILITY AMONG GENOTYPES IN VIGOR AND ROOTING

Abstract: Herbaceous cuttings of Psidium. cattleyanum from the fi eld do not take root. Cuttings of Psidium. cattleyanum resist at temperatures with averages around 39.3 ºC. There is genetic variability justifying the selection of cattley guava genotypes. Mini-cuttings make better rooting, therefore with high variability between genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The pots were filled with the Basaplant® commercial substrate and with single superphosphate fertilizer (6 g L -1 ), limestone (30 g L -1 ) and Osmocote® (6.6 g L -1 ) in the 14-14-14 formulation. Throughout the experiment, the plants were fertilized with 7.6 g urea, 24.7 g single superphosphate and 2.8 g potassium chloride per pot, which were split into three applications at 14-day intervals (Biazatti et al, 2018). Foliar fertilization with Bordeaxu mixture was performed every two weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pots were filled with the Basaplant® commercial substrate and with single superphosphate fertilizer (6 g L -1 ), limestone (30 g L -1 ) and Osmocote® (6.6 g L -1 ) in the 14-14-14 formulation. Throughout the experiment, the plants were fertilized with 7.6 g urea, 24.7 g single superphosphate and 2.8 g potassium chloride per pot, which were split into three applications at 14-day intervals (Biazatti et al, 2018). Foliar fertilization with Bordeaxu mixture was performed every two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The mini-cuttings strategy has provided high rooting rates in Psidium species (Altoé et al, 2013(Altoé et al, , 2011a, which was confirmed in the present study. According to Biazatti et al (2018), the summer was the best time for rooting. Altoé et al (2011) found that 'Cortibel 1' minicuttings had the lowest rooting percentages in the months of June and November.…”
Section: Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, vegetative propagation through root cuttings is one of the alternatives that allow the anticipation of the reproductive stage, reduces the juvenile period of the plants and ensures that their characteristics will be maintained (BIAZATTI et al, 2018). Few researches are using in vivo propagation of Campomanesia in the literature, but its use may be an alternative for the production of clonal nursery trees since great results have been obtained for other species and contributed to fast reproductions of new progenies (KOUAKOU et al, 2016).…”
mentioning
confidence: 99%